Digitize and Punish: Racial Criminalization in the Digital Age by Brian Jefferson (review). - Ludwig, Jason (Technology & Culture, 2023)
Digitize and Punish: Racial Criminalization in the Digital Age By Brian Jefferson. Brian Jefferson's I Digitize and Punish i makes an important contribution to this growing field by examining the intersection of race and computing in an understudied historical case: the development and growth of computerization in the U.S. criminal justice system beginning in the 1960s.